Characteristics and medium-term outcomes of a retrospective cohort of patients with non-malignant, non-cirrhotic splanchnic vein thrombosis. (March 2023) - Gallo, C.; Manna, M.; Cristoferi, L.; Malinverno, F.; Ratti, L.; Gerussi, A.; Carbone, M.; Invernizzi, P.; Ciaccio, A.
Abstract : Introduction: Non-malignant, non-cirrhotic splanchnic vein thrombosis (NC-SVT) is an infrequent yet not negligible cause of portal hypertension (PHT). Despite often associated with myeloproliferative neoplasms (MPN), prothrombotic disorders (PD) or local factors (LF), up to 30% of cases are idiopathic. Long-term management is debated, especially for cases with no underlying factors. Aim: To describe the clinical course and management of a single-centre NC-SVT-patients cohort. Methods: A retrospective analysis of NC-SVT patients referred to our centre between November 2009 and September 2021, with at least three-months follow-up, was performed. Etiology, thrombosis extension, clinical presentation, and therapeutic strategy at SVT onset were retrieved. After referral, clinical, biochemical, and radiological outcomes were analyzed. Results: A total of 22 NC-SVT patients were included (50% male, mean age at referral 53.1 years). Mean follow-up time was 29 months (10-66). The most frequent cause was MPN (31.2%), followed by LF (27.3%), and PD (13.6%). Most SVT (95.5%) involved the portal vein, six of which with spleno/mesenteric extension. One case had isolated intrahepatic involvement. Seven (15%) presented with PHT-related complications (three ascites, four variceal bleeding) and nine (40.1%) developed esophageal varices. All MPS and PD received long-term anticoagulation, except four cases (three excessive bleeding risk, one patient refusal). Most MPS cases (57%) underwent etiological therapy. Eight patients received beta-blockers at SVT onset, four of which as secondary prophylaxis of variceal bleeding. At referral, beta-blockers were added in two cases with radiological/biochemical evidence of PHT progression. During follow-up, four patients developed esophageal varices, but no PHT-related complications occurred. No significant variation from referral of biochemical parameters (platelet count, coagulation, bilirubin, albumin, aminotransferases) was detected. All SVT (100%) were stable/improved, and spleen length showed no significant variation. A single case of extrasplanchnic thrombosis occurred. Conclusions: We report excellent mid-term outcomes in a well-phenotyped NC-SVT-patients cohort. Additional prospective studies are needed.